Sibling narratives of autistic play culture. Issue 6 (3rd July 2017) - Conn, Carmel; Drew, Sharon
Abstract: Though autobiographical accounts illustrate that enjoyable experiences of childhood play are well within the experience of being autistic, published sibling accounts tend not to focus on positive experiences of shared play. This study sought to collect enabling narratives of autism from non-autistic siblings who were asked to remember details of play they enjoyed with their autistic brother or sister and address the question 'How do you understand what happened?'. Single interviews were carried out with three adult siblings and data analysis focused straightforwardly on what was said. Many successful play episodes were narrated with descriptions of play that included elaborate construction play, physical play and pretence. An important way in which participants made sense of play experiences was with reference to ordinary social structures, with judgements made about the appropriateness of play according to norms that operated within specific contexts rather than the innate capacities of their play partner.